Bronchobiliary fistula: a rare complication after biliodigestive surgery for bile duct injury - Chagra-Martínez, Jorge O.; Aguilera-Hernández, Estrella; Castillo-Salazar, María F.; González-Díaz, Jorge I.; Sánchez-Reyes, Karina (International Journal of Research in Medical Sciences, 2022)
A bronchobiliary fistula (BBF) is an abnormal communication between the biliary and bronchial systems. It is a rare condition with an unclear etiology. The principal causes are hepatic hydatid cysts, obstructive and iatrogenic processes. Presenting symptoms are variable and range from productive cough to recurrent pneumonia. The finding of bilioptisis is patognomonic. This case report presented a 22-year-old female patient who underwent a Roux-en-Y hepaticojejunostomy (RYHJ) for a bile duct injury and who later on, developed a bronchobiliary fistula.